Conductive paste and conductive film

By using aqueous inorganic adhesive composed of aluminum hydroxide, phosphoric acid and metal oxides as the adhesive for conductive paste, combined with composite dispersant, the environmental pollution and stability of existing conductive paste are solved, and low-temperature sintering and low-temperature sintering are achieved Cost, green and environmentally friendly conductive film preparation, with excellent stability and conductive properties.

CN116631670BActive Publication Date: 2025-01-14TAN KAH KEE INNOVATION LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310497708.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-05
Publication Date
2025-01-14
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

The existing methods for preparing conductive paste cause serious environmental pollution, and organic resin adhesives produce harmful substances during production and use, affecting the stability of conductive lines.

Method used

Use conductive paste including conductive fillers, inorganic adhesives and dispersants, where the inorganic adhesive consists of aluminum hydroxide, phosphoric acid, metal oxides and water. Use aqueous inorganic adhesives as adhesives and can be sintered at low temperatures, with low cost and environmental protection. and improve printing and film forming properties through compound dispersants.

Benefits of technology

It has achieved low-temperature sintering, low-cost, green and environmentally friendly conductive film preparation, with good stability, conductivity and adhesion, reducing environmental pollution, and improving the density and oxidation resistance of the conductive film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116631670B_ABST
    Figure CN116631670B_ABST
Patent Text Reader

Abstract

The present application discloses a conductive paste and a conductive film, wherein the conductive paste comprises a conductive filler, an inorganic glue and a dispersant, wherein the inorganic glue comprises aluminum hydroxide, phosphoric acid, a metal oxide and water. The adhesive in the conductive paste described in the present application is an aqueous inorganic glue, so that the conductive paste can not only be sintered at a low temperature, but also has high printability, and is low in cost and environmentally friendly. Furthermore, the conductive film prepared from the conductive paste has good stability, conductivity and adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of conductive pastes, and in particular to a conductive paste and a conductive film prepared from the conductive paste. Background Art

[0002] As the third industrial revolution continues to deepen, electrical appliances have occupied every corner of our lives. This means that the number of electrical appliances has increased dramatically, the scale of factories producing electrical appliances has become larger and larger, and the factories have an inevitable impact on the environment during the production process.

[0003] Conductive circuits (conductive films) are key components in electrical appliances. Existing methods for preparing conductive circuits include photolithography, electroplating, and screen printing. Photolithography can prepare conductive circuits with high precision, but it will cause a lot of material waste and environmental pollution. The electroplating process is relatively complicated, and it will also produce a lot of wastewater, polluting the environment. Screen printing technology is easy to operate and low in cost, but the adhesive in the conductive paste mainly used in screen printing is usually glass powder or organic resin adhesive, among which glass powder contains heavy metal lead and has a high sintering temperature; organic resin adhesives will produce a large amount of harmful substances such as styrene, acrylonitrile, phenols, formaldehyde, etc. during production and use, which will cause environmental pollution, and because the temperature of the circuit is high when it is working, the organic resin in the conductive circuit is easy to decompose, causing damage to the conductive circuit.

[0004] Therefore, an environmentally friendly conductive paste is urgently needed. Summary of the invention

[0005] In view of this, the present application provides a conductive paste, aiming to improve the problem of serious environmental pollution of existing conductive pastes.

[0006] The embodiment of the present application is implemented as follows: a conductive paste includes a conductive filler, an inorganic glue and a dispersant, wherein the inorganic glue includes aluminum hydroxide, phosphoric acid, a metal oxide and water.

[0007] Optionally, in some embodiments, in the conductive paste, the content of the conductive filler is 75 to 90 parts, the content of the inorganic glue is 5 to 20 parts, and the content of the dispersant is 5 to 20 parts by weight; and / or

[0008] In parts by weight, in the inorganic glue, the content of aluminum hydroxide is 12 to 18 parts, the content of phosphoric acid is 30 to 35 parts, the content of metal oxide is 0 to 3 parts, and the content of water is 40 to 90 parts.

[0009] Optionally, in some embodiments, the conductive filler includes one or more of copper powder, silver powder, silver-coated copper powder, gold powder and silver-copper alloy powder; and / or

[0010] The metal oxide includes one or more of copper oxide, zinc oxide and magnesium oxide.

[0011] Optionally, in some embodiments, the shape of the conductive filler includes one or more of spherical, rod-shaped, flake-shaped and irregular shapes.

[0012] Optionally, in some embodiments, when the conductive filler is spherical, the average particle size of the conductive filler is 100 to 800 nm; and / or

[0013] When the conductive filler is in a rod-like, sheet-like or irregular shape, the maximum outer diameter of the conductive filler is 1 to 3 μm.

[0014] Optionally, in some embodiments, the dispersant includes one or more of an alcoholamine solvent, an alcohol solvent, and an alcohol ether solvent; or

[0015] The dispersant is a compound dispersant, which includes dispersant A and dispersant B. The dispersant A includes an alcoholamine solvent, and the dispersant B includes one or more of an alcohol solvent and an alcohol ether solvent.

[0016] Optionally, in some embodiments, when the dispersant is the compound dispersant, in the conductive paste, the content of the dispersant A is 5 to 10 parts, and the content of the dispersant B is 5 to 10 parts by weight.

[0017] Optionally, in some embodiments, the alcohol amine solvent includes one or more of ethanolamine, diethanolamine, triethanolamine and 2-amino-2-methyl-1-propanol; and / or

[0018] The alcohol solvent includes one or more of glycerol, ethylene glycol and diethylene glycol; and / or

[0019] The alcohol ether solvent includes one or more of diethylene glycol methyl ether, diethylene glycol butyl ether and ethylene glycol butyl ether.

[0020] Correspondingly, an embodiment of the present application further provides a conductive film, which is obtained by forming and sintering the above conductive paste.

[0021] Optionally, in some embodiments, the sintering temperature is 150-250° C.; and / or

[0022] The sintering time is 5 to 20 minutes.

[0023] The adhesive in the conductive paste described in the present application is a water-based inorganic adhesive, so that the conductive paste can not only be sintered at low temperature, but also has high printability, low cost, and is green and environmentally friendly. Furthermore, the conductive film prepared from the conductive paste described in the present application has good stability, conductivity and adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0025] Figure 1 This is a flow chart of a method for preparing a conductive paste provided in an embodiment of the present application;

[0026] Figure 2 is a flow chart of a method for preparing a conductive film provided in an embodiment of the present application;

[0027] Figure 3 is a resistivity bar graph of the conductive films of the conductive film embodiments 1 to 10 and the conductive film comparative examples 1 to 2 of the present application;

[0028] Figure 4 is a SEM image of the conductive film of conductive film embodiment 1 of the present application;

[0029] Figure 5 is a SEM image of the conductive film of conductive film embodiment 2 of the present application;

[0030] Figure 6 is a SEM image of the conductive film of conductive film embodiment 3 of the present application;

[0031] Figure 7 is a SEM image of the conductive film of conductive film embodiment 4 of the present application;

[0032] Figure 8 is a SEM image of the conductive film of conductive film embodiment 5 of the present application;

[0033] Fig. 9 is a SEM image of the conductive film of conductive film embodiment 6 of the present application;

[0034] Fig.10 is a SEM image of the conductive film of conductive film embodiment 7 of the present application;

[0035] Fig.11 is a SEM image of the conductive film of conductive film embodiment 8 of the present application;

[0036] Fig.12is a SEM image of the conductive film of conductive film embodiment 9 of the present application;

[0037] Fig.13 is a SEM image of the conductive film of conductive film embodiment 10 of the present application;

[0038] Fig.14 is a SEM image of the conductive film of conductive film comparative example 1 of the present application;

[0039] Fig.15 is a SEM image of the conductive film of conductive film comparative example 2 of the present application;

[0040] Fig.16 It is a temperature-resistivity test graph of the conductive film obtained after the conductive paste of Example 6 of the present application is sintered at 150° C., 170° C., 200° C., 250° C., and 300° C.;

[0041] Fig.17 This is a graph showing the anti-aging test results of the conductive paste of conductive film Example 6 and conductive film Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0043] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0044] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0045] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple, respectively.

[0046] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0047] The technical solution of this application is as follows:

[0048] In a first aspect, an embodiment of the present application provides a conductive paste comprising a conductive filler, an inorganic glue and a dispersant, wherein the inorganic glue comprises aluminum hydroxide, phosphoric acid, a metal oxide and water.

[0049] The metal oxide includes, but is not limited to, one or more of copper oxide, zinc oxide and magnesium oxide.

[0050] In the conductive paste, the content of the conductive filler is 75 to 90 parts by weight, the content of the inorganic glue is 5 to 20 parts, and the content of the dispersant is 5 to 20 parts. Within the content range of each component, the conductive paste can have good leveling and thixotropy, so that the conductive film prepared from the conductive paste has low roughness, high density and good conductivity. Furthermore, for conductive films that are easily oxidized, such as copper films, conductive films with high density can have good oxidation resistance and thus good stability.

[0051] In the inorganic glue, the content of aluminum hydroxide is 12 to 18 parts, the content of phosphoric acid is 30 to 35 parts, the content of metal oxide is 0 to 3 parts, and the content of water is 40 to 90 parts by weight. Within the content range of each component, on the one hand, it is beneficial to make the conductive paste including the inorganic glue have better leveling and thixotropy, so that the conductive film prepared by the conductive paste has lower roughness, higher density and better conductivity; on the other hand, it can also make the conductive film prepared by the conductive paste have stronger adhesion to the substrate; on the other hand, it can make the inorganic glue have higher stability, so that the conductive film prepared by the conductive paste has higher stability.

[0052] It can be understood that when the content of the metal oxide in the inorganic glue is 0 parts, it means that the inorganic glue does not contain any metal oxide.

[0053] The conductive filler includes one or more of copper powder, silver powder, silver-coated copper powder, gold powder and silver-copper alloy powder.

[0054] The shape of the conductive filler includes but is not limited to one or more of spherical, rod-shaped, sheet-shaped and irregular shapes. When the conductive filler is spherical, the average particle size of the conductive filler is 100 to 800 nm. When the conductive filler is rod-shaped, sheet-shaped or irregular, the maximum outer diameter of the conductive filler is 1 to 3 μm.

[0055] The dispersant includes, but is not limited to, one or more of an alcoholamine solvent, an alcohol solvent, and an alcohol ether solvent.

[0056] The alcoholamine solvent includes, but is not limited to, one or more of ethanolamine, diethanolamine, triethanolamine and 2-amino-2-methyl-1-propanol.

[0057] The alcohol solvent includes, but is not limited to, one or more of glycerol, ethylene glycol and diethylene glycol.

[0058] The alcohol ether solvent includes, but is not limited to, one or more of diethylene glycol methyl ether, diethylene glycol butyl ether and ethylene glycol butyl ether.

[0059] In some embodiments, the dispersant is a compound dispersant, and the compound dispersant includes dispersant A and dispersant B, wherein the dispersant A includes the above-mentioned alcoholamine solvent, and the dispersant B includes one or more of the above-mentioned alcohol solvent and alcohol ether solvent. The selected dispersants are all environmentally friendly solvents and can be recycled and reused during the curing process of the conductive paste.

[0060] In the compound dispersant, the alcohol amine solvent (dispersant A) can effectively improve the thixotropy of the conductive paste, and the alcohol solvent and the alcohol ether solvent (dispersant B) can effectively reduce the viscosity of the conductive paste. Under the synergistic effect of dispersant A and dispersant B, the conductive paste can have better printability, which is conducive to the preparation of a conductive film with better film-forming properties.

[0061] When the dispersant is the compound dispersant, in the conductive paste, the content of the dispersant A is 5 to 10 parts, and the content of the dispersant B is 5 to 10 parts by weight.

[0062] The adhesive used in the conductive paste described in the present application is the aqueous inorganic glue (inorganic glue whose solvent is water) described above, so that the conductive paste can be sintered at a low temperature and can also have a high printability, so that the conductive film prepared by the conductive paste has good stability, conductivity and adhesion. In addition, the conductive paste described in the present application is low-cost and green and environmentally friendly.

[0063] Second, see Figure 1 The present application also provides a method for preparing a conductive paste, comprising the following steps:

[0064] Step S11: providing an inorganic glue and a dispersant, mixing them to obtain a mixed solution;

[0065] Step S12: adding a conductive filler into the mixed solution and mixing the mixture to obtain a conductive slurry.

[0066] The materials and addition ratios of the inorganic glue, dispersant and conductive filler are as described above and will not be repeated here.

[0067] The mixing method includes but is not limited to ball milling, stirring, homogenization, etc.

[0068] The preparation method of the conductive paste described in the present application is simple, green and environmentally friendly, and the conductive film prepared from the conductive paste described in the present application has good stability, conductivity and adhesion.

[0069] In a third aspect, an embodiment of the present application further provides a conductive film, which is prepared by forming a film and sintering the conductive paste described above.

[0070] Fourth, please refer to Figure 2 The present invention also provides a method for preparing a conductive film, comprising the following steps:

[0071] Step S21: providing a conductive paste, and placing the conductive paste on a substrate to obtain a conductive paste film layer bonded to the substrate;

[0072] Step S22: sintering the conductive paste film layer to obtain a conductive film.

[0073] The conductive paste is as described above and will not be described again here.

[0074] The substrate may be a substrate known for preparing a conductive film, such as a PCB circuit board, a ceramic substrate, and a glass substrate.

[0075] The sintering temperature is 150-250° C., for example, 160-200° C., 180-210° C., 190-220° C., 215-230° C., 225-240° C., etc., and the sintering time is 5-20 min., for example, 6-15 min., 8-16 min., 10-18 min., etc. Within the temperature and time range, it is beneficial to prepare a conductive film with good conductive properties and good stability.

[0076] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0077] Examples 1 to 10

[0078] The components and proportions are shown in Table 1. Among them, dispersant A is triethanolamine, and dispersant B is ethylene glycol.

[0079] Table 1:

[0080]

[0081] Among them, “\” means no addition, and the average particle size of copper powder and silver powder is 400nm.

[0082] Comparative Example 1

[0083] The conductive paste of this comparative example includes 8g copper powder, 1g waterborne polyurethane (organic resin) and 1g ethylene glycol (organic solvent), wherein the average particle size of the copper powder is 400nm.

[0084] Comparative Example 2

[0085] The conductive paste of this comparative example includes 8g of silver powder, 1g of waterborne polyurethane (organic resin) and 1g of ethylene glycol (organic solvent), wherein the average particle size of the silver powder is 400nm.

[0086] Conductive film embodiment 1

[0087] A glass substrate is provided, and the conductive paste in Example 1 is disposed on the glass substrate to obtain a liquid film. The liquid film is placed in a nitrogen environment and sintered at 250° C. for 10 minutes to obtain a conductive film with a thickness of 30 μm.

[0088] Conductive film embodiments 2 to 10

[0089] Conductive film embodiments 2 to 10 are substantially the same as conductive film embodiment 1, except that conductive film embodiments 2 to 10 use the conductive pastes of embodiments 2 to 10 to replace the conductive paste of embodiment 1, respectively.

[0090] Conductive film comparative examples 1 to 2

[0091] Conductive film comparative examples 1-2 are substantially the same as conductive film embodiment 1, except that conductive film comparative examples 1-2 use the conductive pastes of comparative examples 1-2 to replace the conductive paste of embodiment 1, respectively.

[0092] Resistivity test:

[0093] The resistivity test was performed on the conductive film of the conductive film examples 1 to 10 and the conductive film comparative examples 1 to 2. The resistivity test method was a four-probe test, and the test results were Figure 3 .

[0094] Depend on Figure 3 It can be seen that:

[0095] Compared with the conductive film of the conductive film comparative example 1, the conductive films of the conductive film embodiments 1 to 7 have lower resistivity and thus have better conductivity;

[0096] Compared with the conductive film of the conductive film comparative example 2, the conductive films of the conductive film embodiments 8 to 9 have a slightly higher resistivity, and the conductive film embodiment 10 has a slightly lower resistivity. However, in combination with the SEM scanning electron microscope test below, compared with the silver film of the conductive film comparative example 2, the silver films of the conductive film embodiments 8 to 10 are denser, have better adhesion and stronger conductivity. Therefore, the comprehensive performance of the silver film prepared by the silver conductive paste of the conductive film embodiments 8 to 10 of the present application is higher than that of the silver film of the conductive film comparative example 2.

[0097] Adhesion test:

[0098] Adhesion tests were performed on the conductive film embodiments 1 to 10 and the conductive film comparative examples 1 to 2, respectively. The test method was a grid knife test. The test results are shown in Table 2 below.

[0099] Table 2:

[0100]

[0101]

[0102] From Table 2 we can see that:

[0103] Compared with the conductive film of conductive film comparison examples 1 to 2, the conductive films of conductive film embodiments 1 to 10 have the same strength of adhesion. It can be seen that the conductive film prepared by the conductive slurry of the present application can make the conductive film prepared therefrom have better adhesion and can meet the commercial performance requirements of the conductive film.

[0104] SEM scanning electron microscope test:

[0105] The conductive films of the conductive film embodiments 1 to 10 and the conductive film comparative examples 1 to 2 were tested by scanning electron microscope, and the results were respectively Figures 4 to 13 and Figures 14-15 SEM images shown.

[0106] Depend on Figures 4 to 15 It can be seen that: compared with the copper film of the conductive film comparative example 1, the copper films of the conductive film embodiments 1 to 7 are more dense; compared with the silver film of the conductive film comparative example 2, the silver films of the conductive film embodiments 8 to 10 are more dense. It should be noted that, since nanosilver has good fusion, compared with the copper films of the conductive film embodiments 1 to 7, the silver films of the conductive film embodiments 8 to 10 have slightly more voids, but compared with the silver film of the conductive film comparative example 2, the silver films of the conductive film embodiments 8 to 10 are more dense, have better adhesion and stronger conductivity.

[0107] Resistivity test and adhesion test of the conductive paste of Example 6:

[0108] Five portions of the conductive paste of Example 6 were respectively placed on five glass substrates, and then sintered at 150°C, 170°C, 200°C, 250°C, and 300°C for 10 min to obtain conductive film 1, conductive film 2, conductive film 3, conductive film 4, and conductive film 5, respectively. Conductive film 1, conductive film 2, conductive film 3, conductive film 4, and conductive film 5 were respectively tested for resistivity and adhesion, and the test methods were as described above. The resistivity test results of conductive film 1, conductive film 2, conductive film 3, conductive film 4, and conductive film 5 were as follows: Fig.16 ,The adhesion test results are shown in Table 3.

[0109] Depend on Fig.16 It can be seen that the resistivity of the conductive film obtained by sintering the conductive paste at 150°C is the highest, reaching 80μΩ·cm, and the resistivity of the conductive film obtained by sintering the conductive paste at 250°C is the lowest, which can be as low as 10μΩ·cm. It can be seen that there is an optimal value for the sintering temperature of the conductive paste of the present application, and the adhesion of the copper film reaches the optimal value around 250°C.

[0110] Table 3:

[0111] Sintering temperature Adhesion 150℃ 3B 170℃ 4B 200℃ 5B 250℃ 5B 300℃ 4B

[0112] From Table 3 we can see that:

[0113] Conductive film 1, conductive film 2, conductive film 3, conductive film 4 and conductive film 5 all have high adhesion. It can be seen that the conductive slurry of the present application can be sintered within a wider sintering temperature range to prepare a conductive film, and the prepared conductive film can have better adhesion.

[0114] Anti-aging test:

[0115] Take Example 6 and Comparative Example 1 as examples (aging conditions are 120°C, 10h), see Fig.17 The conductive films of the conductive film embodiment 6 and the conductive film comparative example 1 were subjected to anti-aging tests respectively. The test method was aging at 120°C for 10 hours. The test results were as follows: Fig.17 .

[0116] Depend on Fig.17 It can be seen that compared with the conductive film of the conductive film comparison example 1, the conductive film of the conductive film embodiment 6 has a slower increase in resistivity under high temperature environment. In other words, the conductive film of the conductive film embodiment 6 can maintain a low resistivity under high temperature environment. It can be seen that the conductive film prepared by the conductive paste of this embodiment has high aging resistance and high stability under high temperature conditions.

[0117] The conductive paste and conductive film provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A conductive paste, characterized in that: The conductive paste comprises a conductive filler, an inorganic glue and a dispersant, wherein the inorganic glue comprises aluminum hydroxide, phosphoric acid, a metal oxide and water, and the metal oxide is copper oxide; In the inorganic glue, the content of aluminum hydroxide is 12 to 18 parts, the content of phosphoric acid is 30 to 35 parts, the content of metal oxide is greater than 0 parts and less than or equal to 3 parts, and the content of water is 40 to 90 parts; In parts by weight, in the conductive paste, the content of the conductive filler is 75 to 90 parts, the content of the inorganic glue is 5 to 20 parts, and the content of the dispersant is 5 to 20 parts.

2. The conductive paste according to claim 1, characterized in that: The conductive filler includes one or more of copper powder, silver powder, silver-coated copper powder, gold powder and silver-copper alloy powder.

3. The conductive paste according to claim 1, characterized in that: The conductive filler may have a shape of one or more of a sphere, a rod, a sheet, and an irregular shape.

4. The conductive paste according to claim 3, characterized in that: When the conductive filler is spherical in shape, the average particle size of the conductive filler is 100-800 nm; and / or When the conductive filler is in a rod-like, sheet-like or irregular shape, the maximum outer diameter of the conductive filler is 1-3 μm.

5. The conductive paste according to claim 1, characterized in that: The dispersant is one of an alcoholamine solvent, an alcohol solvent and an alcohol ether solvent; or The dispersant is a compound dispersant, which includes dispersant A and dispersant B. The dispersant A includes an alcoholamine solvent, and the dispersant B includes one or more of an alcohol solvent and an alcohol ether solvent.

6. The conductive paste according to claim 5, characterized in that: When the dispersant is the compound dispersant, in the conductive paste, the content of the dispersant A is 5 to 10 parts, and the content of the dispersant B is 5 to 10 parts by weight.

7. The conductive paste according to claim 5, characterized in that: The alcoholamine solvent includes one or more of ethanolamine, diethanolamine, triethanolamine and 2-amino-2-methyl-1-propanol; and / or The alcohol solvent includes one or more of glycerol, ethylene glycol and diethylene glycol; and / or The alcohol ether solvent includes one or more of diethylene glycol methyl ether, diethylene glycol butyl ether and ethylene glycol butyl ether.

8. A method for preparing a conductive film, characterized in that: The conductive film is obtained by forming a film and sintering the conductive paste according to any one of claims 1 to 7.

9. The preparation method according to claim 8, characterized in that: The sintering temperature is 150-250° C.; and / or The sintering time is 5 to 20 min.

Citation Information

Patent Citations

  • Conductive cement or coating composition

    GB959398A

  • Electrically conductive heat-resistant phosphate composite material

    RU2013100503A